2016
DOI: 10.1002/prep.201600058
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Compatibility of the Energetic Binder PolyNIMMO with Energetic Plasticizers: Experimental and DFT Studies

Abstract: The development of energetic binders with suitable energetic plasticizers is required to enhance the mechanical properties and to reduce the glass transition temperature of propellant and explosive formulations. The compatibility of the energetic binder poly(3‐nitratomethyl‐3‐methyloxetane) (polyNIMMO) with five different energetic plasticizers viz. bis(2,2‐dinitro propyl)acetal (BDNPA), dinitro‐diaza‐alkanes (DNDA‐57), 1,2,4‐butanetriol trinitrate (BTTN), N‐N‐butyl‐N‘(2‐nitroxy‐ethyl) nitramine (BuNENA) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…As shown in Figure 3, reactive energetic plasticizer (BNPB) could reduce the GAP pre-polymer viscosity more effectively, as compared to the reactive neutral plasticizer (BEHB). This indicated that REP could be more efficient than the conventional plasticizer during processability [26].…”
Section: Viscosity Studies Of Gap/rpsmentioning
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 3, reactive energetic plasticizer (BNPB) could reduce the GAP pre-polymer viscosity more effectively, as compared to the reactive neutral plasticizer (BEHB). This indicated that REP could be more efficient than the conventional plasticizer during processability [26].…”
Section: Viscosity Studies Of Gap/rpsmentioning
confidence: 91%
“…According to the literature, the click reaction between the polymer and RPs could be done in the catalyst-free condition [26][27][28][29]. So, we examined the catalyst-free synthesis of GAP/RPs (Scheme 2).…”
Section: Synthesis and Characterization Of The Rps And Gap/rpsmentioning
confidence: 99%
“…The heat of explosion of PGN was calculated as 2661 kJ/kg, which was higher than that of PNIMMO (818 kJ/kg) and glycidyl azide polymer (2500 kJ/kg) [1]. PNIMMO is a promising energetic binder for insensitive munitions and has been investigated [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the DSC method can provide compatibility results that are similar to vacuum stability test results for the same combinations [14]. Various works have been done on the compatibility of oxetane-based energetic polymers with contacted materials by the DSC method [15][16][17][18]. In order to achieve at a better understanding of the relationship between the structure and reactivity of these oxetane-based difluoroamino polymers, this paper focuses on the synthesis, characterization and compatibility of PDN with some ingredients which are commonly used in propellants and PBXs, using the DSC method.…”
Section: Introductionmentioning
confidence: 99%